Human leucocyte antigens as prognostic markers in head and neck squamous cell carcinoma - Dyckhoff, Gerhard; Herold-Mende, Christel; Scherer, Sabine; Plinkert, Peter K.; Warta, Rolf (Cancers, 2022)
Background: The induction and regulation of immune responses depend on human leucocyte antigen (HLA) molecules that present peptides derived from mutated neoantigens or tumor-associated antigens to cytotoxic T cells. The natural variation of HLA molecules might differ between tumor patients and the normal population. Thus, there might be associations between the frequencies of HLA alleles and the survival of tumor patients. Methods: This issue was studied in a cohort of 84 patients with head and neck squamous cell carcinomas (HNSCCs) of different localizations. The cohort was followed up for more than 10 years. HLA-A/B/C CTS-PCR-SSP typing at 1 field level from blood samples was performed, and the results were correlated with survival. Results: HLA-A*02 was the most prevalent allele in our cohort and was present in 51.1% of patients. The HLA-A*25 and HLA-C*06 alleles exhibited a significantly higher frequency in cancer patients than in the normal population of 174 blood and kidney donors (p = 0.02 and p = 0.01, respectively, Fisher’s exact test). For HLA-C*04, a negative impact on overall survival in univariate analysis (p = 0.045) and a negative, but statistically insignificant effect on survival toward poorer survival in multivariate analysis (HR: 1.82; 95% CI: 0.99–3.34, p = 0.053) were observed. In addition, HLA-A*02 was also beneficial for overall survival and progression-free survival in multivariate analysis (HR 0.54; 95% CI: 0.31–0.92; p = 0.023). Conclusion: HLA-A*02 allele expression might not only predict better survival but might also indicate superior tumor antigen presentation and, thus, help to select patients who could benefit from T-cell-dependent immunotherapies.
Gesehen am 10.10.2022